Prevalence of measles neutralizing antibody in children under 15 years in southwestern Nigeria (2005)
The immune status of children under 15 years in the Southwestern region of Nigeria against measles virus was determined using the neutralization test with a view to assessing the herd immunity to the virus in these communities. A total of 256 serum samples collected from children were tested by the beta method of neutralization. Forty (15.6%) of these samples were found to be positive at a titre of 1:256, 35 (13.7%) at 1:128, 36(14.1%) at 1:64, 37(14.5%) at 1:32, 38 (14.8%) at 1:16, 27 (10.5%) at 1:8 and 16 (6.3%) at 1:4. Twenty-seven (10.5%) of the 256 samples had no detectable antibody to the measles virus. There was no significant relationship between the antibody titre to measles virus and the gender of the children (p > 0.05). Also, there was no significant difference using Chi square analysis between the neutralizing antibody titres and the age of the children (p > 0.05). All the children whose samples were tested were vaccinated against measles as attested to by their parents. However, the vaccination does not seem to protect all the children, for some of them had no detectable neutralizing antibody while some had low neutralizing antibody titre. In Nigeria, where only a single dose of measles vaccine is given at 9 month, measles may remain a serious threat to the children population with its attendant high morbidity and mortality.